Business Cycle Synchronization in EU: A Time‐Varying Approach. (1st July 2014) - Degiannakis, Stavros; Duffy, David; Filis, George
Abstract This article investigates the time‐varying correlation between the EU12‐wide business cycle and the initial EU12 member‐countries based on Scalar‐BEKK and multivariate Riskmetrics model frameworks for the period 1980–2012. The paper provides evidence that changes in the business cycle synchronization correspond to major economic events that have taken place at a European level. In the main, business cycle synchronization until 2007 had moved in a direction positive for the operation of a single currency, suggesting that the common monetary policy was less costly in terms of lost flexibility at the national level. However, as a result of the Great Recession of 2007 and the subsequent Eurozone Crisis, a number of periphery countries, most notably Greece, have experienced desynchronization of their business cycles with the EU12‐wide cycle. Nevertheless, for most countries, any questions regarding the optimality and sustainability of the common currency area in Europe should not be attributed to a lack of cyclical synchronization.